Nickel Depletion and Agglomeration in SOFC Anodes During Long‐Term Operation. Issue 3 (29th May 2017) - Zekri, A.; Herbrig, K.; Knipper, M.; Parisi, J.; Plaggenborg, T.
Abstract: Low degradation is a key feature for a successful commercialization of solid oxide fuel cell (SOFC) systems. A variety of degradation mechanisms influences the overall degradation rate. Nickel depletion, agglomeration and coarsening in anodes during operation are considered as an important degradation mechanism. In this work, the microstructure of SOFC anodes of electrolyte‐supported cells with operation times up to 20, 000 hours (850 °C) were analyzed. The examined anodes consist of a porous cermet of nickel and gadolinium doped ceria. Scanning electron microscopy (SEM) and energy‐dispersive X‐ray (EDX) analysis were used to investigate the nickel distribution in the anode. The results show nickel depletion at the electrolyte/anode interface, which becomes more noticeable for increased operation time. In addition, nickel agglomeration in the contact layer and in the functional layer was found. A relationship between nickel agglomeration and depletion was deduced.